2007
DOI: 10.5194/hess-11-1309-2007
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory data analysis and clustering of multivariate spatial hydrogeological data by means of GEO3DSOM, a variant of Kohonen's Self-Organizing Map

Abstract: Abstract. The use of unsupervised artificial neural network techniques like the self-organizing map (SOM) algorithm has proven to be a useful tool in exploratory data analysis and clustering of multivariate data sets. In this study a variant of the SOM-algorithm is proposed, the GEO3DSOM, capable of explicitly incorporating three-dimensional spatial knowledge into the algorithm. The performance of the GEO3DSOM is compared to the performance of the standard SOM in analyzing an artificial data set and a hydroche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…Le principe de l' algorithme des SOM consiste à effectuer une classification non linéaire des bases de données complexes en identifiant des groupes semblables. Ainsi, à partir d'un apprentissage non supervisé, cet algorithme recherche itérativement des similarités parmi les données observées et les représente sur une carte de sortie (ou carte de Kohonen) en préservant les voisinages (Peeters et al, 2006). L' apprentissage se fait avec différentes tailles de carte et la taille optimale est choisie en minimisant les erreurs dites de quantification (QE) et de topographie (TE) (Konan et al, 2006 ;Park et al, 2003 …”
Section: Caractérisation Des Processus De Minéralisation Des Eaux Du unclassified
“…Le principe de l' algorithme des SOM consiste à effectuer une classification non linéaire des bases de données complexes en identifiant des groupes semblables. Ainsi, à partir d'un apprentissage non supervisé, cet algorithme recherche itérativement des similarités parmi les données observées et les représente sur une carte de sortie (ou carte de Kohonen) en préservant les voisinages (Peeters et al, 2006). L' apprentissage se fait avec différentes tailles de carte et la taille optimale est choisie en minimisant les erreurs dites de quantification (QE) et de topographie (TE) (Konan et al, 2006 ;Park et al, 2003 …”
Section: Caractérisation Des Processus De Minéralisation Des Eaux Du unclassified
“…The SOM-algorithm as described by Peeters et al (2007) and Choi et al (2014), is used to diagnose the effect of the hydrogeochemical processes and on groundwater quality. The SOM-algorithm is based on unsupervised learning, which means that the desired output is not known a priori.…”
Section: Self-organizing Mapsmentioning
confidence: 99%
“…They concluded that the SOM (nonlinear method) for classification outperformed the linear method (PCA). SOMs have also been applied in evaluating the characteristics of sediment contamination, groundwater quality, soil contamination, and ecological communities (Alvarvez-Guerra et al 2008;Peeters et al 2006;Sanchez-Martos et al 2002;Song et al 2007;Subida et al 2013;Voyslavov et al 2012). Although the advantages of the SOM algorithm and its ability for classification and visualization of large environmental datasets is evident (Astel et al 2007), the results obtained through SOM analysis are only semiquantitative for the interpretation of such (Simeonova et al 2010).…”
mentioning
confidence: 97%